Analysis of cariogenic and erosive potential of pediatric antiepileptic liquid medicaments: An In vitro study - M Deepthi; Mallayya C Hiremath; S K Srinath; J Nagarathna (Wolters Kluwer Medknow Publications, 2018)
Introduction: Epilepsy affects seventy million people worldwide. India accounts for 10%-20% (5-10 million) of the global burden of epilepsy. The prevalence of dental caries is significantly higher in epileptic children. Antiepileptic pediatric liquid medicaments (PLMs) are commonly prescribed and are easily accepted by children. However, these drugs can place children at risk for dental caries and dental erosion, when used on a regular basis and over a long period. Aim: The aim of this study was to analyze the cariogenic and erosive potential of pediatric anti-epileptic LMs. Material and Methods: Ten pediatric antiepileptic LMs which are most commonly used in children for a prolonged period were obtained from local pharmacies after consulting pediatricians of Bengaluru city. Physicochemical analysis for endogenous pH, viscosity, and sugar content of these antiepileptic PLMs was done. Data obtained were subjected to statistical analysis using SPSS software. One-way ANOVA, post hoc test, and t-test were used for the statistical analysis. Results: Most of the antiepileptic PLMs analyzed showed low pH, high viscosity, and higher total sugar content. Statistically significant differences (P = 0.001) were found among the PLMs in terms of pH, viscosity, and sugar content. Conclusions: Most of the antiepileptic PLMs showed cariogenic and erosive potential. Thus, the study highlights the need to reformulate the antiepileptic PLMs with sugar substitutes or making it sugar free.